Subclinical atherosclerosis and cardiovascular events among patients with colorectal cancer - Levy, Julia; Kazemian, Elham; Ramin, Cody; Loroña, Nicole C.; Nadri, Maimoona; Gasho, Jordan O.; Silos, Katrina D.; Nikolova, Andriana P.; Dey, Damini; Siegel, Erin M.; Gigić, Biljana; Hardikar, Sheetal; et al. (Cancer medicine, 2025)
Background Prior studies have documented that patients with colorectal cancer (CRC) are at an increased risk of cardiovascular disease (CVD). Objectives To examine coronary artery calcium (CAC) as a marker of subclinical atherosclerosis and its association with major adverse cardiovascular events (MACE) in patients with CRC across the cancer treatment trajectory. Methods Adults with newly diagnosed CRC were enrolled in the prospective ColoCare study from 2017 to 2024. CAC was measured from routine diagnostic computed tomography (CT) and positron emission tomography-CT scans at CRC diagnosis until 5 years post-diagnosis. Atherosclerosis was defined as the presence of CAC. We used multivariable-adjusted Fine and Gray models to assess the association between CAC and MACE risk, accounting for competing risks. Results Among 300 CRC patients, the most common CVD risk factors at cancer diagnosis were hypertension (37%), hyperlipidemia (24%), and diabetes (14%). During follow-up (median = 5.3 years), 75 (25%) individuals experienced MACE: stroke (3%), new/worsening HF (9%), HF exacerbation requiring hospitalization (2%), coronary revascularization (3%), and death (19%). Among individuals with imaging at baseline (n = 101), 37 (36.6%) had CAC, and statins were not prescribed in 11 (55.0%) patients with moderate/high CAC. For those with serial imaging (n = 61), 31.1% showed worsening CAC and 3% developed new CAC. Baseline CAC conferred a higher risk of MACE (HR = 4.79; 95% CI: 1.05-21.75, p = 0.04) after accounting for cancer-related deaths as a competing risk. Conclusions Subclinical atherosclerosis and MACE are common among patients with CRC. Integrating CAC from routine cancer imaging can identify patients who may benefit from cardio-preventive treatment.
Gesehen am 20.10.2025